Analysis and Design of Magnetic Shielding System for Breast Cancer Treatment with Hyperthermia Inductive Heating - Chanchai Thongsopa; Thanaset Thosdeekoraphat (International Journal of Antennas and Propagation)
An analysis and design of magnetic shielding system are presented for breast cancer treatment with hyperthermia inductive heating. It is a technique to control magnetic field intensity and relocate the heating area by using a rectangular shielding with aperture. The distribution of the lossy medium was analyzed using the finite difference time domain method. Theoretical analyses investigate whether a novel shielded system is effective for controlling the magnetic field distribution or heating position. Theoretical and experimental investigations were carried out using a lossy medium. The inductive applicator is a ferrite core with diameter of 7 cm, excited by 4 MHz signal and a maximum output power of 750 W. The results show that size of heating region can be controlled by varying the aperture size. Moreover, the investigation result revealed that the position of heating region can be relocated by changing the orientation of the ferrite core with shielded system in x-axis direction. The advantage of the magnetic shielding system is that it can be applied to prevent the side effects of hyperthermia cancer treatment by inductive heating.